The story of a cheat - Borchard, Adolphe 1882-1967 (<<The>> Criterion collection, 2010)
"Considered Sacha Guitry’s masterpiece, this fleet, witty picaresque about a gambler and petty thief is a whimsical delight. Guitry himself stars as the tricheur looking back fondly on a life of crime, which he narrates with an effervescence matched by that of the film's skillful editing and cinematography. With its rapid storytelling and novel use of voice-over, "The story of a cheat" has influenced filmmakers from Orson Welles to François Truffaut." [criterion.com]
Original: Frankreich 1936
Bildformat 1.33:1
Keywords: Film; DVD-Video